Introduction: Self in South Asia. Issue 1 (21st March 2013) - Mookherjee, Nayanika
Abstract The so called western, rational, individual, autonomous, self marked by freedom, potential and choice and deemed essential for modernity has predominantly been juxtaposed with the presumed collective, static, bounded, "identity" of the "non‐west" and its inhabitants. Anthropological scholarship has thus been marked by its focus on the "identity" of its subjects (drawn from a collective and shared with others) instead of a self. Nowhere has this theorisation between the self and the collective been so fraughtly interrogated as in the Anthropology of South Asia. A common place occurrence in academic, policy and everyday discussions, South Asian personhood has been comprehended only through various collective categories like gender, kinship, religion, caste, community following the Dumontian holism that there are no individuals and only caste and hierarchy in India. The discussions of self have also remained understudied in historiography inspite of being intrinsic to the Indian post‐colonial public life. Recently, historians have turned to individual sensibilities and life stories while others have argued that the self is a product of history transformed in a public debate. It is important to reflect on the methodological connotations of using such person‐centred self‐representations – narratives, novels, biographies and memoirs – which are often deemed to be inadequate sources of anthropological and ethnographic value. Theoretically and methodologically these articles on self in South Asia distinctly depart from the existing anthropological and historical literature by bringing together at the same juncture both synchronic and diachronic accounts in conjunction with psychic and social histories. In this volume we are interested in the practices and conceptual tools behind the self than a definition. The focus here is on the ethnographic examination of the self and personal experience, of the minutae of the interactions of daily life, on the dialogical characters of the self in South Asia rather than a "South Asian" self. The idea of the self becomes particularly pertinent within the shifting contexts of economic liberalization, migration, violent conflicts, consumerism, new media and the role of transnationally affiliated groups in challenging/reifying static, orientalised and essentialising accounts of the self.